P=4πlr²
r²=P/4πl
r=√(P/4πl)= 1/2*(√(P/πl)
Answer is A
(1 - 2x)⁴
(1 - 2x)(1 - 2x)(1 - 2x)(1 - 2x)
[1(1 - 2x) - 2x(1 - 2x)][1(1 - 2x) - 2x(1 - 2x)]
[1(1) - 1(2x) - 2x(1) - 2x(-2x)][1(1) - 1(2x) - 2x(1) - 2x(-2x)]
(1 - 2x - 2x + 4x²)(1 - 2x - 2x + 4x²)
(1 - 4x + 4x²)(1 - 4x + 4x²)
1(1 - 4x + 4x²) - 4x(1 - 4x + 4x²) + 4x²(1 - 4x + 4x²)
1(1) - 1(4x) + 1(4x²) - 4x(1) - 4x(-4x) - 4x(4x²) + 4x²(1) - 4x²(4x) + 4x²(4x²)
1 - 4x + 4x² - 4x + 16x² - 16x³ + 4x² - 16x³ + 16x⁴
1 - 4x - 4x + 4x² + 16x² + 4x² - 16x³ - 16x³ + 16x⁴
1 - 8x + 24x² - 32x³ + 16x⁴
Hi, to find the area of the rectangle all you have to do is multiply the length times the width.
A = 80inches • 45inches = 3600
There are two zeros: -3 and -1. This is because when you factor f(x)<span>= x^2 + 4x + 3, it becomes f(x) = (x + 3)(x + 1). In order to find the zeros, set f(x) to 0, and then solve for x for both (x + 3) and (x + 1). You can check your answer by substituting either -3 or -1 for x in the equation 0 = </span>x^2 + 4x + 3.